Chemodivergent synthesis of multi-substituted/fused pyrroles via copper-catalyzed carbene cascade reaction of propargyl α-iminodiazoacetates. Issue 84 (3rd October 2016) - Zhang, Cheng; Chang, Sailan; Qiu, Lihua; Xu, Xinfang
Abstract : A novel cascade reaction via γ-imino carbene is developed, which provides access to pyrroles in high yield with structure diversity. Abstract : A novel cascade reaction of alkynyl-tethered α-iminodiazoacetates has been developed, which provides a general access to both multi-substituted and fused pyrroles in high yields with a broad substrate scope. The γ-imino carbene is proposed as the key intermediate in this divergent reaction and followed by unpresented transformations.